Effect of Solvent Polarity and pH on the Phenolic Content and Antioxidant Activity of Aronia melanocarpa L. Extracts - Ciftci, Harun; Caliskan, Cigdem Er; Öztürk, Kübra; Akıncı, Zehra (My University, 2026)
This study aims to determine the effectiveness of different solvent systems, particularly acidified ones, in extracting polyphenolic compounds from Aronia melanocarpa (A. melanocarpa) fruit and to assess their effects on antioxidant capacity. Extractions were performed at a 1:20 solid/liquid ratio using systems consisting of 50% ethanol (EtOH), 50% methanol (MeOH), pure water, and their acidified counterparts (with 2% HCl (v/v)). The resulting extracts were evaluated for antioxidant capacity based on total phenolic content (TPC), total flavonoid content (TFC), and single electron transfer (SET)-based assays, including ABTS, DPPH, and FRAP. The highest TPC value was observed in the acidified MeOH extract (62.20 mg GAE/g dw), while the highest TFC was obtained from the acidified EtOH extract (5.26 mg QE/g dw). In the DPPH assay, the same acidified MeOH extract exhibited the highest Trolox equivalent value and showed a statistically significant difference compared to the other groups (p<0.001). Similarly, acidified extracts demonstrated stronger antioxidant activity in both ABTS and FRAP assays. All antioxidant methods showed a positive correlation with phenolic and flavonoid contents. Polyphenolic profiling of A. melanocarpa by LC–MS/MS (acidified MeOH extract) revealed chlorogenic acid and quinic acid as predominant metabolites. These findings indicate that low-pH solvents enhance the solubility of phenolic compounds and improve extraction efficiency. In addition to polarity, chemical parameters such as pH, hydrogen bonding capacity, and proton-donating ability should also be considered when selecting an appropriate extraction medium.
Keywords: Gıda Bilimi ve Teknolojisi; Bitki Bilimleri